Perception of nurse administrators regarding electronic nursing documentation - Chand, Sulakshana; Sarin, Jyoti (International Journal of Research in Medical Sciences, 2017)
Background: Nurses represent the largest profession in the healthcare. Always present at patient’s bedside, nurses weave together many facets and create order in the work environment. In addition to providing direct patient care, nurses are also responsible for recording the nursing activities. Handwritten documents however, run a risk of being inconsistent and unstructured often leading to omission of pertinent patient data which may ultimately impact nursing interventions and patient outcomes. Research studies continue to reveal substandard nursing documentation. Hence, nurse administrators today are challenged to achieve; outstanding outcome measures; highest quality quartile ratings for patient care; stellar accreditation performance and various other quality measures. Therefore, development of strategies to improve quality of nursing documentation remains a top priority among nurse administrators. In order to accomplish this, moving from paper to electronic clinical documentation system may be a key tool. For almost two decades, electronic health records have become increasingly popular. Although nurses’ perception regarding electronic nursing documentation is one of the most important indicators of the application of nursing information system, it is however, equally important to explore the perception of nurse administrators regarding electronic nursing documentation. The purpose of this study was to explore the perceptions of nurse administrator’s regarding electronic nursing documentation. Methods: A descriptive study was undertaken to explore the perception of 26 nurse administrators working in a teaching hospital. A valid and reliable perception assessment scale was developed to generate data. The collected data was analysed using descriptive analysis. Results: Findings revealed that nearly half of the nurse administrators reported a moderately favourable perception towards electronic nursing documentation. Conclusions: It was concluded that overall nurse administrators have a positive perception of electronic nursing documentation which would be beneficial in promoting a positive organization climate towards the acceptance of electronic health records.